TECHNOWARE AS A CATALYST FOR CUSTOMER RETENTION IN SOUTH-SOUTH NIGERIA’S MANUFACTURING INDUSTRY - Udofia, Effiong Anietie; Etuk, Okon Iniobong (International Research Journal of Arts and Communication, 2025)
This study examined the effect of technoware deployment on customer retention of manufacturing firms in South-South, Nigeria. The study employed the simple random sampling technique. A sample size of 149 was determined from a population of 238 staff of the studied manufacturing firms in South- South, Nigeria using the Taro Yamane formula. The Ordinary Least Square regression analysis was used to test the effect of the relationship between the two variables. Result shows that the deployment of customer relation management software and cloud computing webapplication had significant effects on customer retention manufacturing firms in South- South, Nigeria. It was concluded that customer relation management software deployment and cloud computing web-application deployment have significant positive effects on customer retention of manufacturing firms in South-South, Nigeria. The researchers recommended among others that service organizations should provide customer relation management software training to all employees to be able to consistently utilize the system for maximum result